An input-output framework for analysing relationships between economic sectors and water use and intersectoral water relationships in Morocco - Abdeslam Boudhar; Said Boudhar; Aomar Ibourk (Journal of Economic Structures, 2017)
Over the last few decades, Morocco has been undergoing a strong and fast water demand increase due to demographic upsurge, irrigated agriculture expansion, flourishing foreign trade and changing standard of living and lifestyles. The continued increase of water demand has imposed a height pressure over national scare water resources. Despite this worrying situation, the imperative of sustainable water use and management has created a need for compulsory information to define and implement economic and water-saving policies in an integrated and informed manner. This paper uses an input-output model of water use to analyse the relationships between economic sectors and water resources use in Morocco (i.e. direct water use) as well as the intersectoral water relationships (i.e. indirect water use). The results show that, on the one hand, Agriculture, hunting and forestry sector exhibits high direct water use. On the other hand, secondary and tertiary sectors display low direct use and high indirect water use. Typical examples of sectors with high indirect water use are manufacture of food and tobacco products and hotels and restaurants sectors. Further by means of the impact analysis, we have demonstrated that the economic sectors whose indirect water use coefficients are high have a significant influence on water resources by means of their 'drag effect' on water use of other sectors. The results highlight the added value of conducting an analysis of the intersectoral water relationships and suggest that it is important to take into account in the processes of policy definition not only the direct water use but also the indirect water use, because neglecting them could threaten our water resources.
Keywords: 330; Scare water resources; Input-output model of water use; Economic sectors; Sustainable water use